Adverse reactions to whole blood donation, basic human needs and nursing diagnoses: a reflection - Gabriela Feitosa Esplendori (SciELO, 2018)
ABSTRACT A theoretical-Reflective study with the objective to reflect on human needs regarding the imbalance of whole blood donors considering adverse reactions to the donation, and the existing nursing diagnoses that best meet the imbalance needs. The following needs were pointed out according to the signs and symptoms of adverse reactions and based on the Theory of Basic Human Needs: skin and tissue integrity, emotional security, pain perception, body mechanics, oxygenation, physical integrity, physical comfort, elimination, neurological, electrolytic and vascular regulation. By observing NANDA International's Definitions and Classifications, adaptations to the existing nursing diagnoses and suggestions for new headings have been proposed. We conclude that some of the needs are interrelated, such as vascular regulation, oxygenation and physical integrity. Thus, more contextualized nursing diagnoses related to the needs of whole blood donors are needed, given the specific nature of the situation generating imbalances such as: ineffective systemic vascular regulation characterized by self-reported dizziness, cutaneous pallor and arterial hypotension related to vasovagal reaction.